Fireside tales: understanding experiences of previous eruptions and factors influencing the decision to evacuate from activity of Volcán de Fuego - Ailsa Naismith; M. Teresa Armijos; Edgar Antonio Barrios Escobar; William Chigna; I. Matthew Watson (Volcanica, 2020)
Volcán de Fuego (Guatemala) is capable of large (VEI≥2) explosive eruptions like that of June 2018, which triggered pyroclastic flows that devastated the community of San Miguel Los Lotes, causing hundreds of fatalities and severe long-term socio-economic impacts. Future volcanic risk mitigation efforts are likely to involve temporary evacuation of local communities, the success of which requires co-operation between locals, scientists, and decision-makers. However, how locals' experiences of eruptive activity influence their responses to evacuation has not been studied in detail. We investigated these themes through semi-structured interviews that focussed on direct experience as opposed to volcanic risk perception, revealing substantial differences between scientists' and locals' observations of Fuego’s activity. Furthermore, a disparity emerged between communities on Fuego's west and east flanks in terms of direct prior eruption experience and communication with authorities. These findings have serious implications for future evacuation efforts at Fuego and at other highly populated volcanoes.